SCIENTIFIC VIEWS ON THE HISTORIOGRAPHY OF THE EMERGENCE OF WRITING - Normatova Firuza Amonovna (Scholar Express Journal, 2025)
If we take a look at the history of the emergence of writing, we can see that the discoveries and inventions of each era did not eliminate writing from society. On the contrary, these inventions compelled people to repeatedly refer to recorded information for further progress. Thanks to writing, humanity was able to understand and learn about its ancestors and pave the way for future struggles. Writing enabled people to unite into communities. Many ancient peoples were unaware that their language was recorded not with letters but with images, symbols, syllabic rules, and phonetic signs. It can even be said that the issue of deciphering these signs remains relevant for researchers to this day. The use of material, pictorial, and symbolic writing at the dawn of human society clearly indicates that the peoples who employed it played a significant role in the formation of civilization.
Keywords: writing; symbols; images